2007
DOI: 10.1177/0883073807306263
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Head Circumference Growth as a Function of Autism Diagnosis and History of Autistic Regression

Abstract: Several reports indicate that autism spectrum disorder (ASD) is associated with increased rate of head growth in early childhood. Increased rate of growth may index aberrant processes during early development, may precede the onset of symptoms, and may predict severity of the disease course. We examined rate of change in occipitofrontal circumference measurements (abstracted from medical records) in 28 boys with ASD and in 8 boys with developmental delay without autism from birth to age 36 months. Only childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 46 publications
(89 reference statements)
8
79
1
3
Order By: Relevance
“…One head circumference study of 28 males with autism (11 with regression) did not report an association between onset status and rate of head growth in the first year of life (19). It is likely that the substantially larger sample size and retrospective longitudinal data in the present study provided greater statistical power to detect differences in the pattern of head growth.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…One head circumference study of 28 males with autism (11 with regression) did not report an association between onset status and rate of head growth in the first year of life (19). It is likely that the substantially larger sample size and retrospective longitudinal data in the present study provided greater statistical power to detect differences in the pattern of head growth.…”
Section: Discussionmentioning
confidence: 75%
“…Although there are a number of complexities in determining onset status (18), children with autism can be characterized as regression (REG) or no regression (nREG), using parent report of early development. The neural underpinnings of onset status remain unclear because only one study has yet examined this question, in a small sample (19).…”
mentioning
confidence: 99%
“…As such, the atypical functional organization of language found in the current study may be due to the aberrant neurodevelopmental processes which have been recently identified in ASD. Recent studies demonstrated that rapid, excessive brain growth occurs in the first years of life in autism (Courchesne et al, 2003;Dementieva et al, 2005;Webb et al, 2007). In the Courchesne et al study, head circumference measures showed that autistic newborns were in the 25th percentile for head size at birth, which was significantly smaller than the normative sample.…”
Section: Early Brain Growth Abnormalities and Lateralization Of Languagementioning
confidence: 94%
“…In a recent longitudinal study, Webb and colleagues examined the rate of head circumference growth (extracted from medical records) of a group of boys with ASD and a group with developmental delay over the first three years of life (Webb et al, 2007). They found that there was a significantly higher rate of growth in the ASD group -more specifically, a statistically significant increase in occipitofrontal circumference between 7 and 10 months, relative to norms.…”
Section: Macrocephalymentioning
confidence: 99%